Selective Metal Chelation by a Thiosemicarbazone Derivative Interferes with Mitochondrial Respiration and Ribosome Biogenesis in Candida albicans - Duan, Ximeng; Xie, Zhiyu; Ma, Liying; Jin, Xueyang; Zhang, Ming; Xu, Yuliang; Liu, Yue; Lou, Hongxiang; Chang, Wenqiang (Microbiology spectrum, 2022)
The increasing incidence of fungal infections and resistance to existing antifungals call for the development of broad-spectrum antifungals with novel mechanisms of action. In this study, we demonstrate that a thiosemicarbazone derivative 19ak selectively inhibits mitochondrial respiration mainly by retarding mitochondrial respiratory chain complex I activity through iron chelation and inhibits ribosome biogenesis mainly by disrupting intracellular zinc homeostasis in C. albicans . Metal chelation is generally considered as a promising antifungal approach but its specific mechanisms are unclear. Here, we identify 13 thiosemicarbazone derivatives that exert broad-spectrum antifungal activity with potency comparable or superior to that of fluconazole in vitro by screening a small compound library comprising 89 thiosemicarbazone derivatives as iron chelators. Among the hits, 19ak exhibits minimal cytotoxicity and potent activity against either azole-sensitive or azole-resistant fungal pathogens. Mechanism investigations reveal that 19ak inhibits mitochondrial respiration mainly by retarding mitochondrial respiratory chain complex I activity through iron chelation, and further reduces mitochondrial membrane potential and ATP synthesis in Candida albicans . In addition, 19ak inhibits fungal ribosome biogenesis mainly by disrupting intracellular zinc homeostasis. 19ak also stimulates the activities of antioxidant enzymes and decreases reactive oxygen species formation in C. albicans , resulting in an increase in detrimental intracellular reductive stress. However, 19ak has minor effects on mammalian cells in depleting intracellular iron and zinc. Moreover, 19ak exhibits low capacity to induce drug resistance and in vivo efficacy in a Galleria mellonella infection model. These findings uncover retarded fungal mitochondrial respiration and ribosome biogenesis as downstream effects of disruption of iron and zinc homeostasis in C. albicans and provide a basis for the thiosemicarbazone 19ak in antifungal application. IMPORTANCE The increasing incidence of fungal infections and resistance to existing antifungals call for the development of broad-spectrum antifungals with novel mechanisms of action. In this study, we demonstrate that a thiosemicarbazone derivative 19ak selectively inhibits mitochondrial respiration mainly by retarding mitochondrial respiratory chain complex I activity through iron chelation and inhibits ribosome biogenesis mainly by disrupting intracellular zinc homeostasis in C. albicans . In addition, 19ak exhibits low capacity to induce fungal resistance, minimal cytotoxicity, and in vivo antifungal efficacy. This study provides the basis of thiosemicarbazone derivative 19ak as a metal chelator for the treatment of fungal infections.